2020
DOI: 10.1177/0266666920967979
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-based advisory services for sustainable agriculture: Assessing farmers’ information behavior

Abstract: Mobile-based advisory services have significant benefits, including access to agricultural information, knowledge sharing, meteorological information, marketing-related information, and financial services for smallholder farmers. This study aimed to assess farmers’ information behavior regarding mobile-based advisory services and how farmers with different characteristics and attitudes access and adopt information. Data were collected from 382 farmers in Dakhalia governorate, Egypt. The most frequently receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Krell et al [32] stated that political considerations and weakness of the infrastructures are of the main limitations for adaptive responses of the farming communities against the climate change impacts. Similar findings have been reported by the researchers from other countries including Zambia [52] and Egypt [53]. To be specific, most of these studies suggest that, in order to provide easier and better meteorological information to farmers, first, inter-institutional cooperation between stakeholders should be increased.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Krell et al [32] stated that political considerations and weakness of the infrastructures are of the main limitations for adaptive responses of the farming communities against the climate change impacts. Similar findings have been reported by the researchers from other countries including Zambia [52] and Egypt [53]. To be specific, most of these studies suggest that, in order to provide easier and better meteorological information to farmers, first, inter-institutional cooperation between stakeholders should be increased.…”
Section: Discussionsupporting
confidence: 81%
“…These researchers, however, suggest that educated farmers can be a turning point to change these negative perspectives towards weather information. Kassem et al [53] reported similar results for the adoption of climate-related predictions in Egypt. Salite [55] also introduced the tradition and negative attitude towards new climate prediction systems as one of the main limiting factors of applying weather services in Mozambique.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The United States dominates the list with 95 documents and 2419 citations, followed by England (26) with 820 citations. China has published 48 documents with 564 citations, followed by the Canada (8), Australia (13), Taiwan (17), Germany (16), Turkey (21), Netherlands (6), and South Korea (22). This data can provide a benchmark for mobile marketingrelated research for other countries.…”
Section: Figure 5 the Country Co-authorship Network Of Mobile Marketi...mentioning
confidence: 98%
“…In addition, mobile marketing strategy also can be incorporated with environmental studies such as weather [16] and also in agriculture business [17]. For mobile marketing in weather, mobile marketing can provide information for the customers about the weather conditions before making their purchase.…”
Section: Background Studymentioning
confidence: 99%